Seed Treatment With Systemic Fungicides: Time for Review - Ayesha, Mulla S.; Suryanarayanan, Trichur S.; Nataraja, Karaba N.; Prasad, Siddegowda Rajendra; Shaanker, Ramanan Uma (Frontiers in Plant Science, 2021)
Pre-sowing seed treatment with systemic fungicides is a firmly entrenched practice for most agricultural crops worldwide. The treatment is intended to protect the crop against seed- and soil-borne diseases. In recent years, there is increasing evidence that fungicidal applications to manage diseases might inadvertently also affect non-target organisms, such as endophytes. Endophytes are ubiquitously present in plants and contribute to plant growth and development besides offering resistance to biotic and abiotic stresses. In seeds, endophytes may play a role in seed development, seed germination, seedling establishment and crop performance. In this paper, we review the recent literature on non-target effects of fungicidal applications on endophytic fungal community and discuss the possible consequences of indiscriminate seed treatment with systemic fungicide on seed endophytes. It is now well recognized that endophytes are ubiquitously present in all parts of the plant, including the seeds. They may be transmitted vertically from seed to seed as in many grasses and/or acquired horizontally from the soil and the environment. Though the origins and evolution of these organisms in plants are a matter of conjecture, numerous studies have shown that they symbiotically aid in plant growth and development, in nutrient acquisition as well in protecting the plants from abiotic and biotic stresses. Against this background, it is reasonable to assume that the use of systemic fungicides in seed treatment may not only affect the seed endophytes but also their attendant benefits to seedling growth and establishment. While there is evidence to indicate that fungicidal applications to manage plant diseases also affect foliar endophytes, there are only few studies that have documented the effect of seed treatment on seed-borne endophytes. Some of the convincing examples of the latter come from studies on the effect of fungicide application on rye grass seed endophyte AR37. More recently, experiments have shown that removal of seed endophytes by treatment with systemic fungicides leads to significant loss of seedling vigour and that such losses could be partially restored by enriching the seedlings with the lost endophytes. Put together, these studies reinforce the importance of seed endophytes to seedling growth and establishment and draw attention on how to trade the balance between the benefits of seed treatments and the direct and indirect costs incurred due to loss of endophytes. Among several approaches, use of reduced-risk fungicides and identifying fungicide-resistant endophytes are suggested to sustain the endophyte contribution to early seedling growth.